Tinjauan Systematic Literature Review Tentang Microlearning: Tren dan Implikasi Teknologi dalam Konteks Pendidikan - M, Nanda Adrian; Armas, Yaumil Maghfirah; Amri, Huriyah Anisah; Arifin, Arifah Novia (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2025)
This study aimed to analyze the trends, technologies, and implications of microlearning in educational contexts through a systematic literature review approach. Data were collected from 197 articles indexed in the Scopus database between 2023 and 2025 and filtered using the PRISMA protocol, resulting in 32 relevant publications. The findings indicate a significant increase in microlearning studies in 2025, with primary concentrations in higher education, healthcare, and vocational training. Microlearning has proven effective in enhancing digital competence, self-efficacy, and learning motivation through the integration of technologies such as video-based instruction, mobile learning, and augmented reality. It also contributes to professional development for educators, language learning, and sustainable digital literacy. This study provides a conceptual foundation for developing adaptive, technology-supported instructional designs and serves as a basis for more inclusive and contextual digital education policies. Ultimately, it contributes by mapping current developments in microlearning, identifying strategic research gaps, and offering evidence-based insights to guide future innovations, implementations, and policymaking in digital education.